Optimalisasi Retribusi Pelayanan Parkir pada Dinas Perhubungan di Kabupaten Gowa - Abdullah, Wahyuningsih; Alyas, Alyas; Usman, Jaelan (Universitas Muhammadiyah Makassar, 2020)
This study aimed to determine, Optimization of Parking Service Levies at the Transportation Department in Gowa Regency. Data collection techniques used observation, interview and documentation. While the informants in this study were 4 people who were the head of the terminal and parking section, the head of the traffic management facility infrastructure, and the Parking Attendant. Data analysis techniques used data reduction, data presentation and verification. The results of this study indicated that the Optimization of Parking Service Retribution at the Transportation Department in Gowa Regency had been carried out optimally because the achievement of the realization of the target had been going well. One form of parking supervision in an effort to collect fees was done directly and coordinated by field officers. This purposed to fulfill whether the implementation of tasks in accordance with the plans that had been set in strengthening the process of collecting parking service fees.